2023
DOI: 10.1590/1519-6984.248755
|View full text |Cite
|
Sign up to set email alerts
|

The role of purslane in modulating diverse effects of high fat diet on biochemical, histological, and molecular parameters of rats’ liver

Abstract: Consuming a high-fat diet causes a harmful accumulation of fat in the liver, which may not reverse even after switching to a healthier diet. Different reports dealt with the role of purslane as an extract against high-fat diet; meanwhile, it was necessary to study the potential role of fresh purslane as a hypolipidemic agent. This study is supposed to investigate further the potential mechanism in the hypolipidemic effect of fresh purslane, by measuring cholesterol 7a-hydroxylase (CYP7A1) and low-density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Jung et al [43] investigated the efects of a diet containing 5% and 10% purslane powder on high-fat diet-induced obese mice and demonstrated reduced weight gain and visceral fat with a high dose after 12 weeks. In a diferent study, administering fresh purslane for eight weeks reduced the adipose tissue weight in obese albino rats [44]. However, Won and Kim found no signifcant efect of orally administering 75 and 125 mg/kg of the ethanol extract of purslane for four weeks on weight gain and feed intake in male C57BL/6J mice with high-fat diet-induced obesity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Jung et al [43] investigated the efects of a diet containing 5% and 10% purslane powder on high-fat diet-induced obese mice and demonstrated reduced weight gain and visceral fat with a high dose after 12 weeks. In a diferent study, administering fresh purslane for eight weeks reduced the adipose tissue weight in obese albino rats [44]. However, Won and Kim found no signifcant efect of orally administering 75 and 125 mg/kg of the ethanol extract of purslane for four weeks on weight gain and feed intake in male C57BL/6J mice with high-fat diet-induced obesity.…”
Section: Discussionmentioning
confidence: 94%
“…Te supplementation of purslane has also been linked to the upregulation of hepatic peroxisome proliferator-activated receptor (PPAR)-α [43,52], which is known to suppress the growth and differentiation of adipocytes while promoting lipolysis and fatty acid oxidation [53]. As another potential mechanism, fresh purslane could increase hepatic cholesterol 7ahydroxylase (CYP7A1) expression and, subsequently, bile acids formation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Purslane could also increase hepatic cholesterol 7a hydroxylase (CYP7A1) expression and, as a result, bile acids production. ( 58 ) Bile acids appear to improve various MetS-related parameters. ( 59 ) Bioactive components in purslane, including carotenoids, flavonoids, saponins, omega 3 s, and thiamine, may contribute to its anti-obesity effects.…”
Section: Discussionmentioning
confidence: 99%
“…Seif et al [54] observed that purslane reduced liver damage caused by H 2 O 2 , as evidenced by a substantial reduction in ALT and AST levels in serum blood and liver homogenates and increased total protein and albumin levels. Additionally, Mousa et al [57] found that supplementation with fresh purslane, particularly at a concentration of 75%, protects against the harmful effects of a high-fat diet at both the cellular and organ levels. In addition, the evaluated liver functions, thyroid hormones, and cholesterol profile improved.…”
Section: Serum Biochemical Parametersmentioning
confidence: 99%